Maurice Spector, James R. Cannon, and the Origins of Canadian Trotskyism - Palmer, Brian (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2005)
Abstract The international historiography of communism has been revived by the availability of previously unexamined sources in the Moscow Archives and an outpouring of new writing. Debates abound, but in Canada the study of communism has generated less new work, and little controversy. This article addresses the contentious issues of Comintern bureaucratism, Stalinization, and the transformation of the revolutionary left in the 1920s by examining the political histories of Maurice Spector and James P. Cannon. As the two major figures in Canadian and United States communism who repudiated Stalinism and embraced Trotskyism in late1928, their struggle to keep the revolutionary potential of Bolshevism alive highlights success as well as failure, offering a comparative look at the importance ofthe subjective realm in the building of a left opposition.